ANALYSIS OF CUSTOMER SATISFACTION LEVELS REGARDING SERVICE QUALITY AND POLICY RISK COVERAGE VALUE AT PT. FAMILY TAKAFUL INSURANCE - Sakinah Sakinah; Wahyu Syarvina (Jurnal Ekonomi, 2023)
Takaful insurance is sharia insurance that aims to minimize losses from a risk. One of its superior products is Fulnadi, this product is devoted to preparing children in terms of education up to bachelor's degree. This study aims to determine how the level of customer satisfaction with the quality of service and the value of the policy risk coverage at PT. Family Takaful Insurance. This study uses a qualitative and quantitative approach that is descriptive analysis. The data taken were library research and field research, using interview data collection techniques and questionnaire techniques. The results of the study revealed that Family Takaful Insurance. Judging from the results of the analysis, customers were satisfied with the quality of service at PT. Family Takaful Insurance and Judging from the results of the analysis that customers are satisfied with the policy risk coverage at PT. Family Takaful Insurance.